If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 10x + 10 Reorder the terms: -2 + 12x = 10x + 10 Reorder the terms: -2 + 12x = 10 + 10x Solving -2 + 12x = 10 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -2 + 12x + -10x = 10 + 10x + -10x Combine like terms: 12x + -10x = 2x -2 + 2x = 10 + 10x + -10x Combine like terms: 10x + -10x = 0 -2 + 2x = 10 + 0 -2 + 2x = 10 Add '2' to each side of the equation. -2 + 2 + 2x = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 10 + 2 2x = 10 + 2 Combine like terms: 10 + 2 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 4x-10=3x+38 | | 2w-1.5= | | 5x-11=136 | | 3w+2y+8x+3x-11y+3w= | | 8x+2=6x+20 | | x(x-x)(x-x)-x*x=110 | | 1.4x+1.2x-3.8=9 | | -.5x+0y=14 | | 3(x+(180-x))-70=200 | | C=kpv+v | | 6x-14=21+x | | -4(5y-5)+2(3y+9)= | | 2(1-10n)=-2(10n-9) | | x(x-x)2-x*x=110 | | (3x+5)(x-1)=0 | | y=2x(3x) | | m+109+26=180 | | 5d-8=-28 | | (2X+85)= | | 4x+11+6x=2+x-9 | | x(9x-7)=(9x+8)(x-3) | | 4x+8x+11y+2w+3x-2y= | | k(k)=y | | 5x=4+-.1y | | 0=56+7x | | 0.16(18x+30)-8x= | | 4x-7w= | | 13s-234=3s-14 | | 10a-2b=-26 | | 2(9+x)=-15(4+x) | | -6=h/18 | | (7x-6)=6-7x |